Changes in absolute alpha power during execution, imagination and observation of a finger movement task - Inacio, Pedro Augusto; Machado, Sérgio; Carrijo dos Santos, Danielly; Albernaz, Thiago; Iransé Oliveira Silva, Iransé; Sardinha Leonardo, Patrícia; Caroline Rodrigues, Anne; Brandão Lopes-Martins, Rodrigo Alvaro; das Águas Caixeta, Davi; Lucas Lima, João; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Neurons that fire both during execution and observation of a motor act, called mirror neurons, provide strong evidence of its existence in humans. Real, observed and imagined movements seem to share most of the same neural pathways. However, little is known about the neural mechanisms and functional processes of the different areas and the integration of information between the observation and imagined systems. Objective: Compare alpha absolute power levels in sensorimotor areas between real, imagined and observed movement conditions. Methods: The sample consisted of a group of 12 healthy young individuals (4 men and 8 women), right-handed and with mean age of 30 ± 10. The task consisted of 4 blocks of 20 trials of rhythmic flexion-extension movements of the index finger by pressing the left button of a mouse properly fixed on a table. The activation level was analyzed by measuring the absolute power of the alpha band (8-13hz). Results: ANOVA with repeated measures showed that in the real condition, alpha absolute power was higher in the electrodes Cz, P3 and Pz compared to the electrode C3. In the imagined condition, the electrodes P3 and Pz presented higher alpha absolute power compared to the electrode C3. For the observed condition, electrodes P3, Pz and P4 presented higher alpha power compared to the electrode C3. In addition, higher alpha absolute power was observed in the electrode Pz compared to the electrodes Cz and C4. Conclusion: Higher alpha activation was observed on the electrode C3 in all conditions. These findings indicate that the observed movement also shares neural circuits when compared to the real and imagined movements. It was observed that in all conditions there was a significant decrease in alpha power on the C3 electrode, which indicates activation of the motor cortex in a similar way in the conditions.